Knowledge, reason, and taste : Kant's response to Hume - Guyer, Paul, 1948- (Princeton University Press, 2008)
Immanuel Kant famously said that he was awoken from his "dogmatic slumbers," and led to question the possibility of metaphysics, by David Hume's doubts about causation. Because of this, many philosophers have viewed Hume's influence on Kant as limited to metaphysics. More recently, some philosophers have questioned whether even Kant's metaphysics was really motivated by Hume. In Knowledge, Reason, and Taste, renowned Kant scholar Paul Guyer challenges both of these views. He argues that Kant's entire philosophy--including his moral philosophy, aesthetics, and teleology, as well as his metaphys